The Constitutional Implications of Drones, Facial Recognition Technology and CCTV - Weaver, Russell (Public Governance, Administration and Finances Law Review, 2022)
Over the centuries, new forms of surveillance technology have emerged. At the founding of the U.S., the government did not have sophisticated spying and surveillance technologies at its disposal. In the eighteenth century, the police might have tried to eavesdrop on their fellow citizens in taverns or other public settings, or they might have listened outside a suspect’s window. However, without the advanced technologies that exist today, the opportunities for successful eavesdropping were very limited. Today, surveillance technologies have gone high tech, creating Orwellian possibilities for snooping. As one commentator observed as far back as 1974, “rapid technological advances and the consequent recognition of the ‘frightening paraphernalia which the vaunted marvels of an electronic age may visit upon human society’ have underlined the possibility of worse horrors yet to come”. This article examines how the U.S. courts are dealing with three different types of technology: CCTV, facial recognition and drones.